沥青混合料保温车螺旋输送机结构设计和仿真 - 高长银; 虞正平; 吴晓铃 (Jixie chuandong)
For the screw conveyor of the asphalt mixture insulation vehicle,by means of the mathematical methods the axial movement speed and the circumferential speed of the screw conveyor are derived,and then the calculation formula of the spiral shaft rotation speed,helical blade diameter and pitch are deduced.According to the calculation formula,the design parameters of the screw conveyor of the asphalt mixture insulation vehicle are calculated.Finally,by using of Engineering Fluid Dynamics software the material flow analysis model of the screw conveyor is established,and the flow field of asphalt mixing material is simulated.The results show that the screw conveyor can stir and mix the materials,as a result of exit space limitation the material is dumped by screw extrusion and should minimize the extend size.The reference for the selection,design and optimization of the screw conveyor will be provided by the research results.